Imperial alchemy nationalism and political identity in Southeast Asia - Reid, Anthony (Cambridge University Press, 2010)
In this book Anthony Reid, one of the premier scholars of Southeast Asia, explores the mysterious alchemy by which new political identities have been formed. Taking Southeast Asia as his example, Reid tests contemporary theory about the relation between modernity, nationalism and ethnic identity.